Mekanisme Investasi Reksadana Syariah melalui Aplikasi Bibit Perspektif Fatwa DSN NO.20/DSN-MUI/IV/2001 - Zahrotul Jannah; Dita Askhatika Putri; Uswatun Chasanah (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2023)
One of the muamalah activities that is not prohibited in Islam as long as it does not violate Sharia principles is investment. Nowadays, there are many applications that make investing easier, such as Bibit. Bibit is an application and one of the investment instruments, namely sharia mutual funds. The aim of this research is to find out whether the Bibit application in carrying out the sharia mutual fund investment mechanism is in accordance with the DSN fatwa No.20/DSN-MUI/IV/2001. This research uses a qualitative method which uses a method of analyzing a case. The results of this research show that Sharia mutual fund investments in seed applications comply with the provisions of DSN fatwa No.20/DSN-MUI/IV/2001. Mudharabah contracts and wakalah contracts are contracts used in operational activities.